IMPLEMENTATION OF THE SEM-PLS APPROACH TO ANALYZE THE IMPACT OF SOCIAL AID AND APBD ON POVERTY IN THE BOJONEGORO DISTRICT - Nurdiansyah, Denny; Novitasari, Diah Ayu; Ridho, Sari Lestari Zainal; Utomo, Muchammad Chandra Cahyo; Oktafiya, Dewi Putri Nur (PATTIMURA UNIVERSITY, 2025)
Poverty is the socio-economic condition of individuals or groups whose fundamental rights to maintain and develop a decent life are unmet. The poverty rate in Bojonegoro was 12.21% in 2022. In order to solve this problem, a poverty model is needed to serve as a reference for the further development of Bojonegoro district. This study aimed to determine the impact of social aid and APBD on poverty in Bojonegoro district. The methodology used in this study is his SEM-PLS quantitative research modeling of poverty using the WarpPLS application. The data sources for this study are the following secondary data in the form of Bojonegoro District Poverty Data, Area Appropriations Budget (APBD), and Social Aid (Bansos) from 2019 to 2022. Survey data were accessed online through the official website. Information from the Central Bureau of Statistics (BPS) and Satu Data Bojonegoro website. The results of this study show that SEM-PLS was applied correctly, and satisfactory results were obtained in terms of overall fit size, measured fit size, and structural fit size. The analysis results show that the variable APBD significantly impacts poverty with a proportion of -0.91. It means that the higher the realization of APBD, the lower the existing poverty rate. Social Aid variables up to -0.09 do not significantly impact poverty. It means that the amount of social benefits you receive does not affect poverty. The conclusion is that the factors that influence poverty in Bojonegoro district are its APBD variables.